Here are all the steps, and what they do:
STEP 1: HORIZONTAL TRANSLATION
We transform
![x^2\mapsto (x-1)^2](https://tex.z-dn.net/?f=x%5E2%5Cmapsto%20%28x-1%29%5E2)
The general transformation is
![f(x)\mapsto f(x+k)](https://tex.z-dn.net/?f=f%28x%29%5Cmapsto%20f%28x%2Bk%29)
These transformations translate the graph horizontally, k units to the left if k>0, k units to the right if k<0.
In this case, k = -1, so we translate the original graph 1 unit to the right.
STEP 2: VERTICAL STRETCH
We transform
![(x-1)^2\mapsto 3(x-1)^2](https://tex.z-dn.net/?f=%28x-1%29%5E2%5Cmapsto%203%28x-1%29%5E2)
The general transformation is
![f(x)\mapsto kf(x)](https://tex.z-dn.net/?f=f%28x%29%5Cmapsto%20kf%28x%29)
These transformations stretch the graph vertically. The graph expands if |k|>1, while it shrinks if 0<|k|<1. If k is negative, we also reflect the graph with respect to the x axis.
In this case, k = 3, so we stretch the graph vertically by a factor 3.
STEP 3: VERTICAL TRANSLATION
We transform
![3(x-1)^2\mapsto 3(x-1)^2+4](https://tex.z-dn.net/?f=3%28x-1%29%5E2%5Cmapsto%203%28x-1%29%5E2%2B4)
The general transformation is
![f(x)\mapsto f(x)+k](https://tex.z-dn.net/?f=f%28x%29%5Cmapsto%20f%28x%29%2Bk)
These transformations translate the graph vertically, k units up if k>0, k units down if k<0.
In this case, k = 4, so we translate the graph 4 units up.
So, we start from the original graph of
and we:
- Translate it 1 unit to the right
- Stretch it vertically by a factor 3
- Translate it 4 units up
(the order is important!)
to get the graph of ![g(x)=3(x-1)^2+4](https://tex.z-dn.net/?f=g%28x%29%3D3%28x-1%29%5E2%2B4)